Importation of band head spin for superdeformed bands in mass region A ∼ 60 - 90 using the variable moment of inertia model - K. A. Gado (Ядерна фізика та енергетика)
We are currently applying the variable moment of inertia model to nuclei in mass region A ∼ 60 - 90 in order to improve spectroscopic analysis of its rotational bands in the superdeformed region, which in turn is helpful in the band head spin prediction and other spins for superdeformed bands. The moment of inertia of the ground state, ϑ0 and restoring force constant, C, were calculated by fitting the observed transition energies. The band head spin, I0 was determined in terms of the ratio of transition energies, verified by root mean square deviations. We verified that the observed high spin superdeformed bands display a near-rigid rotor behavior by studying transition energies over twice the angular momentum (RTEOS). The calculated and observed transition energies agree well.